Potential therapeutic effects of Chinese meteria medica in mitigating drug-induced acute kidney injury - Li, Jun; Li, Tonglu; Li, Zongping; Song, Zhiyong; Gong, Xuezhong (Frontiers in Pharmacology, 2023)
Drug-induced acute kidney injury (DI-AKI) is one of the leading causes of kidney injury, is associated with high mortality and morbidity, and limits the clinical use of certain therapeutic or diagnostic agents, such as antineoplastic drugs, antibiotics, immunosuppressants, nonsteroidal anti-inflammatory drugs, and contrast media. In recent years, numerous studies have shown that many Chinese herbal medicines, active ingredients derived from Chinese herbal medicines, and herbal formulas confer protective effects against DI-AKI by targeting a variety of cellular or molecular mechanisms, such as oxidative stress, inflammatory processes, cell necrosis, apoptosis, and autophagy. This review summarizes the research status of common DI-AKI with Chinese herbal medicine interventions, including cisplatin, gentamicin, contrast agents, methotrexate, and acetaminophen. At the same time, this review introduces the active ingredients with application prospects represented by ginseng saponins, tetramethylpyrazine, Panax notoginseng saponins, and curcumin. Overall, this review provides a reference for the development of promising nephroprotectants.